Energy expenditure characteristics of weight lifting: 2 sets to fatigue - Scott, C. B.; Leary, M. P.; TenBraak, A. J. (Applied Physiology, Nutrition, and Metabolism, 2011)
We investigated the work performed and energy expenditure characteristics within and among 2 sets of the bench press at 70%, 80%, and 90% of 1 repetition maximum (1RM). For both sets fatigue was the end point. We asked: do multiple sets affect subsequent work output along with aerobic, anaerobic, and excess postexercise oxygen consumption (EPOC) contributions? Ten males participated. Work was significantly less for the 2nd set within the 70% and 80% protocols, but not the 90% protocol. Anaerobic (glycolytic) energy expenditure was less for the 2nd set within all protocols. However, within all protocols, the work / energy expenditure ratio was not different between sets. Overall work was significantly different among protocols, becoming less as the weight lifted was increased: 70%, 637.1 ± 122.4 J; 80%, 512.4 ± 93.4 J; 90%, 324.7 ± 92.6 J (p < 0.001). EPOC was not different among protocols after the 1st set, 2nd set, or combined overall. Moreover, the overall EPOC did not correlate with overall work performed (r = 0.31, p = 0.11). EPOC overall did correlate with aerobic (r = 0.68, p < 0.001) and anaerobic (r = 0.65, p < 0.001) energy expenditures. In terms of a work / energy expenditure ratio, the least amount of completed work at 90% 1RM required greater energy expenditure as compared with 70% and 80% because of an EPOC that is similar for all. As more work is completed (i.e., lower weight, more repetitions), aerobic and anaerobic exercise energy expenditures appear to increase accordingly, yet absolute EPOC remains essentially unchanged, contributing less to the overall energy expenditure.